Efficient Access to the Core of the Strychnos, Aspidosperma and Iboga Alkaloids. A Short Synthesis of Norfluorocurarine - Martin, David B. C.; Vanderwal, Christopher D. (Journal of the American Chemical Society, 2009)
An efficient anionic bicyclization of tryptamine-derived Zincke aldehydes forms the basis for a three-step route to the tetracyclic ABCE core of many Strychnos, Aspidosperma, and Iboga alkaloids. This powerful reaction is showcased in a five-step synthesis of the Strychnos alkaloid norfluorocurarine from tryptamine and pyridine.